2019
DOI: 10.1063/1.5109317
|View full text |Cite
|
Sign up to set email alerts
|

Electrical current switching of the noncollinear antiferromagnet Mn3GaN

Abstract: We report electrical current switching of noncollinear antiferromagnetic (AFM) Mn 3 GaN/Pt bilayers at room temperature. The Hall resistance of these bilayers can be manipulated by applying a pulse current of 1.5 × 10 6 A/cm 2 , whereas no significant change is observed up to ∼ 10 8 A/cm 2 in Mn 3 GaN single films, indicating that the Pt layer plays an important role. In comparison with ferrimagnetic Mn 3 GaN/Pt bilayers, a lower electrical current switching of noncollinear AFM Mn 3 GaN is demonstrated, with a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(34 citation statements)
references
References 44 publications
3
31
0
Order By: Relevance
“…Another possibility would be a double helical AFM MnP 59 and CrAs 60 , which have 1.3µ B /Mn and 1.7µ B /Cr, respectively, and it is worthy of future research on those AFM switching. We note that the similar order of switching current density has been recently realized in the SOT of noncollinear AFM of MGN(2.43 µ B /Mn) and Mn 3 Sn(3.2 µ B /Mn 61 ) with 1.5 and 5 × 10 6 A/cm 2 , respectively 16,17 . Since STT consumes more energy than SOT in traditional STT and SOT of FM 62 , our results may imply that SOT in such AFMs has a great potential to realize even lower current density switching.…”
Section: Smallsupporting
confidence: 79%
“…Another possibility would be a double helical AFM MnP 59 and CrAs 60 , which have 1.3µ B /Mn and 1.7µ B /Cr, respectively, and it is worthy of future research on those AFM switching. We note that the similar order of switching current density has been recently realized in the SOT of noncollinear AFM of MGN(2.43 µ B /Mn) and Mn 3 Sn(3.2 µ B /Mn 61 ) with 1.5 and 5 × 10 6 A/cm 2 , respectively 16,17 . Since STT consumes more energy than SOT in traditional STT and SOT of FM 62 , our results may imply that SOT in such AFMs has a great potential to realize even lower current density switching.…”
Section: Smallsupporting
confidence: 79%
“…In addition to the resistance modulation of collinear antiferromagnets, the electrical switching of noncollinear antiferromagnetic memory devices was achieved as well. Hajiri et al reported the switching of the magnetic order parameter of the noncollinear antiferromagnet Mn 3 GaN through an electric current in an experiment in 2019 ( Figure ) 46. They found that the manipulation of the Hall resistance in the Mn 3 GaN/Pt bilayer can be induced by a pulse current, which disappeared in the single Mn 3 GaN layer, and thus inferred the switching of noncollinear Mn 3 GaN antiferromagnet is caused by the spin–orbit torque.…”
Section: Introductionmentioning
confidence: 99%
“…Hajiri et al reported the switching of the magnetic order parameter of the noncollinear antiferromagnet Mn 3 GaN through an electric current in an experiment in 2019 (Figure 3). [46] They found that the manipulation of the Hall resistance in the Mn 3 GaN/Pt bilayer can be induced by a pulse current, which disappeared in the single Mn 3 GaN layer, and thus inferred the switching of noncollinear Mn 3 GaN antiferromagnet is caused by the spin-orbit torque. This work demonstrates the possibility of electrical switching of a noncollinear antiferromagnet using the spin-orbit torque.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The spin current can be generated from a non-metal bottom layer through the spin Hall effect. Recently, such a spin-Hall torque switching has been reported in the GaNMn 3 (001)/Pt bilayer structure [75]. In this experiment that AFM switching was detected using a conventional AMR effect, since the noncollinear AFM Γ 5g phase in Mn 3 GaN does not support the AHE [29].…”
mentioning
confidence: 76%